2009
DOI: 10.1097/hjr.0b013e32831fd6c8
|View full text |Cite
|
Sign up to set email alerts
|

French registry of cases of type I acute aortic dissection admitted to a cardiac rehabilitation center after surgery

Abstract: Physical training of moderate intensity seems feasible and beneficial in postsurgical type I aortic dissection patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
68
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(68 citation statements)
references
References 14 publications
0
68
0
Order By: Relevance
“…This, along with the likely prevalence of new‐onset anxiety and/or depression after AAD, suggests that cardiac rehabilitation after discharge may be beneficial. A study by Corone et al showed that cardiac rehabilitation after discharge, for patients experiencing a type A AAD, improved functionality, allowed patients to return to work earlier, increased muscular strength, and improved mental well‐being . In addition, patients expressed a desire for specific activity recommendations and felt that consequent activity restriction reduced their quality of life, suggesting a need for better patient education and further research to develop specific activity guidelines for this patient cohort.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This, along with the likely prevalence of new‐onset anxiety and/or depression after AAD, suggests that cardiac rehabilitation after discharge may be beneficial. A study by Corone et al showed that cardiac rehabilitation after discharge, for patients experiencing a type A AAD, improved functionality, allowed patients to return to work earlier, increased muscular strength, and improved mental well‐being . In addition, patients expressed a desire for specific activity recommendations and felt that consequent activity restriction reduced their quality of life, suggesting a need for better patient education and further research to develop specific activity guidelines for this patient cohort.…”
Section: Discussionmentioning
confidence: 99%
“…Avoidance of sexual activity was also common postdissection and is unnecessary, with the most common reason reported being fear. Health care providers should evaluate sexual health and allay this unfounded fear.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, only 1 study to date has evaluated the safety and efficacy of exercise‐based cardiac rehabilitation in post‐AD patients. Corone et al reported on 33 French patients (25 men, 8 women) with type 1 DeBakey AD (mean age, 55.1 years) who underwent cardiac rehabilitation soon after surgical repair (mean, 27 days). Average resting SBP at hospital discharge was 120 mm Hg; most of the patients (97%) were taking β‐blockers.…”
Section: Physical Activity and Exercisementioning
confidence: 99%
“…Follow-up was for 1 year and included 3 complications in 2 patients that required additional thoracic surgery, although no deaths, cerebrovascular accidents, or myocardial infarctions were recorded. Ten of the 19 patients (53%) of working age were able to return to work ( 20 ). Th ese data substantiate the feasibility, relative safety, and eff ectiveness of exercise-based cardiac rehabilitation in post-AD survivors.…”
Section: Invited Commentarymentioning
confidence: 52%